2016
DOI: 10.5455/msm.2016.28.353-356
|View full text |Cite
|
Sign up to set email alerts
|

Level of Competencies of Family Physicians in Kosovo from Different Perspectives

Abstract: Aim:The aim of this analysis was to compare the level of self-perceived competencies of primary health care physicians in Kosovo with patients’ viewpoint, as well as the necessary (required) level of such competencies from decision-makers’ standpoint.Methods:Three cross-sectional studies were carried out in Kosovo in 2013 including: i) a representative sample of 1340 primary health care users aged ≥18 years (49% men; overall mean age: 50.5±17.9 years; response rate: 89%); ii) a representative sample of 597 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…There were no sex-differences with regard to the perceived levels of family physicians' competencies according to patients' standpoint. As pointed out earlier, this finding related to a high level of family physicians' knowledge and competencies is in line with the very positive assessment of the quality of primary health care services among our study participants (13). Thus, in our study, 75% of participants perceived as "good" or "very good" the medical encounter, a finding which is quite different from a previous study conducted in Gjilan region, Kosovo, in 2010 including a representative sample of 1039 primary health care users (14).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There were no sex-differences with regard to the perceived levels of family physicians' competencies according to patients' standpoint. As pointed out earlier, this finding related to a high level of family physicians' knowledge and competencies is in line with the very positive assessment of the quality of primary health care services among our study participants (13). Thus, in our study, 75% of participants perceived as "good" or "very good" the medical encounter, a finding which is quite different from a previous study conducted in Gjilan region, Kosovo, in 2010 including a representative sample of 1039 primary health care users (14).…”
Section: Discussionsupporting
confidence: 91%
“…The assessment instrument administered in our study sample showed a very high internal consistency, which was similar in male and female participants. As a matter of fact, the overall internal consistency in our survey (Cronbach's alpha=0.96) was higher than in a prior cross-cultural adaptation exercise conducted in Kosovo, which reported an overall Cronbach's alpha=0.88 (11). In addition, the internal consistency in the current study conducted in Kosovo was higher than in a previous validation study conducted in Albania (9).…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations